2022
DOI: 10.1007/s10734-022-00896-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher education and the importance of values: evidence from the World Values Survey

Abstract: The collection of data on values through instruments such as the World Values Survey has focused attention on two opposing but inter-related trends, namely the combination of substantial cultural change in many countries and the persistence of distinctive traditional values. This reflects the interplay between social changes associated with modernisation and globalisation—including increased global trade and the rise of global popular culture—with traditional values country-specific systems. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…However, this is different by gender in that the importance of friends decreases more strongly for men than for women in old age (Kalmijn, 2012). Moreover, education and marital status are relevant: Higher educational attainment significantly affects the propensity to view friends and leisure as important, whereas no substantial differences were found between graduates and non-graduates regarding the tendency to view family and work as important (Koshy et al, 2023).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, this is different by gender in that the importance of friends decreases more strongly for men than for women in old age (Kalmijn, 2012). Moreover, education and marital status are relevant: Higher educational attainment significantly affects the propensity to view friends and leisure as important, whereas no substantial differences were found between graduates and non-graduates regarding the tendency to view family and work as important (Koshy et al, 2023).…”
Section: Introductionmentioning
confidence: 94%
“…An observed change in the value of life course domains that potentially conflicts with family formation might give evidence for a change in priorities at the individual level. Depending on the purpose and field of study, there is a great diversity and breadth in the definition of life domains (Koshy et al, 2023;Matei & Abrudan, 2018). In the scope of this research, we focus on four main aspects of life domains; namely, family, leisure, work, and friends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each society has its own set of values and all individuals should adopt those values [75] (p. 23). With the use of six broad values: family, friends, leisure, work, politics, and religion, defined by Matei and Abrudan [76], Koshy et al [6] examined trends in assessment of their importance. They found that over the multiyear collection horizon for the World Values Survey, changes in the respondents' views on values at the national level occurred more quickly in countries undergoing major sustained changes, principally economic ones.…”
Section: Values Of a Great Universitymentioning
confidence: 99%
“…The values of a university represent its unique platform and mode of operation, and at the same time, they are both a distinct inspirational and limitative factor of the entire effort of modern higher education [6][7][8][9][10]. Values are the first phenomena researched in the paper.…”
Section: Introductionmentioning
confidence: 99%